"Do Internal Due Process System Permit Adequate Political and Moral Space for Ethics Voice, Praxis, and Community?" - Nielsen, Richard P. (Journal of business ethics, 2000)
Internal due process systems are the formal mechanisms thatmany organizations use to address and resolve ethics conflicts.Problematical due process systems such asinvestigation-punishment and grievance-arbitration systemsnarrowly constrain the political and moral space needed formeaningful ethics voice, praxis, and community. The relativelyuncommon employee board and mediator-counselor types of systemscan help solve such problems. The employee board andmediator-counselor systems permit questioning not only of guiltwith respect to policy violations but also the appropriateness ofthe policies as well as potential biases in an organization'sembedded tradition-system that may be contributing to unethicalbehavior. Theoretical implications for organization ethics,praxis, community, and integrative social contracts theories areexplored. Several case examples are discussed.